(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The effective functioning of combine harvesters is crucial for the agricultural industry, especially in the harvesting of grain crops, which is vital for food security and economic stability. This study examines the replacement intervals of travelling unit spare parts in combine harvesters, employing data gathered from 87 combine harvesters across nine brands in various districts of Bangladesh. The study seeks to deliver quantitative insights into these essential components’ lifespan and replacement requirements, emphasizing the monitoring of running hours and replacement intervals. The data analysis indicates considerable discrepancies in replacement intervals across various spare components and types of harvesters. The research revealed that approximately 45% of the harvesters required new sprockets, with head feed (HF) models exhibiting greater wear than full feed (FF) models. Nearly 47% of crawlers required replacement due to prolonged usage. Approximately 24% of rollers required replacement, with the majority exceeding 600 hours of usage. Conversely, 96% of carrier rollers remained in satisfactory condition without requiring replacement, indicating their durability. One-third (33%) of rear rollers needed replacement, with HF models requiring earlier substitutions than FF versions. Approximately 18% of guides were substituted, with HF models exhibiting reduced lifespans. Merely 10% of tension frames needed modifications, whereas HF models demanded modifications more frequently. HF harvesters necessitated repairs and component replacements more frequently, whereas FF harvesters exhibited greater longevity before needing maintenance. This study provides essential insights for industry stakeholders and policymakers when deciding equipment maintenance and management methods. J Bangladesh Agril Univ 23(2): 231-240, 2025